Multi-omics integration identifies cell-state-specific repression by PBRM1-PIAS1 cooperation - Patric J. Ho; Junghun Kweon; Laura A. Blumensaadt; Amy E. Neely; Elizabeth Kalika; Daniel B. Leon; Sanghyon Oh; Cooper W.P. Stringer; Sarah M. Lloyd; Ziyou Ren; Xiaomin Bao (Elsevier, 2024)
Summary: PBRM1 is frequently mutated in cancers of epithelial origin. How PBRM1 regulates normal epithelial homeostasis, prior to cancer initiation, remains unclear. Here, we show that PBRM1's gene regulatory roles differ drastically between cell states, leveraging human skin epithelium (epidermis) as a research platform. In progenitors, PBRM1 predominantly functions to repress terminal differentiation to sustain progenitors' regenerative potential; in the differentiation state, however, PBRM1 switches toward an activator. Between these two cell states, PBRM1 retains its genomic binding but associates with differential interacting proteins. Our targeted screen identified the E3 SUMO ligase PIAS1 as a key interactor. PIAS1 co-localizes with PBRM1 on chromatin to directly repress differentiation genes in progenitors, and PIAS1's chromatin binding drastically diminishes in differentiation. Furthermore, SUMOylation contributes to PBRM1's repressive function in progenitor maintenance. Thus, our findings highlight PBRM1's cell-state-specific regulatory roles influenced by its protein interactome despite its stable chromatin binding.